2017
DOI: 10.3126/jpahs.v4i1.24664
|View full text |Cite
|
Sign up to set email alerts
|

Post-infective glomerulonephritis in children: a hospital based study

Abstract: Introductions: Post-infective glomerulonephritis (PIGN) is a common pediatric kidney disease in developing countries. This hospital based study aim to analyze clinical profile of PIGN in children in local scenario. Methods: This was a descriptive review of medical records of children admitted with a diagnosis of PIGN at Patan Hospital in three years period during 2013 to 2016. Hospital medical records were reviewed for demographic profiles, clinical features, laboratory data, treatment, and complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 9 publications
6
13
1
1
Order By: Relevance
“…In this study showed more cases of PIGN in male individuals which were comparable to other studies 3,15,16 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study showed more cases of PIGN in male individuals which were comparable to other studies 3,15,16 .…”
Section: Discussionsupporting
confidence: 92%
“…Those patients presented with renal impairment were older than 10 years of age. A study of PIGN on children showed 31.7% of the patients had renal impairment at presentation 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A number of studies have already been reported in Nepal on acute glomerulonephritis in children, one of which reported that acute glomerulonephritis comprised 3.1% of annual pediatric admissions. [6][7][8] The aim of this study was to explore the clinico-laboratory features and complications of acute glomerulonephritis among paediatric patients in Chitwan Medical College Teaching Hospital, Chitwan.…”
Section: Introductionmentioning
confidence: 99%
“…Sama halnya dengan penelitian Lufyan et al 8 yang melaporkan bahwa kelompok usia yang paling banyak menderita GNAPS ialah di atas 5 tahun yaitu 5-9 tahun. Menurut Shah et al 11 di katakan kelompok usia yang paling banyak menderita GNAPS ialah lebih dari 5 tahun yaitu berada pada kelompok usia sekolah yaitu 5-15 tahun.…”
Section: Bahasanunclassified